2021
DOI: 10.1001/jamanetworkopen.2021.1558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Concurrent Functional Vision and Hearing Impairment and Association With Dementia in Community-Dwelling Medicare Beneficiaries

Abstract: IMPORTANCE Impairments in vision or hearing are common and have been independently linked to higher risk of dementia in older adults. There is a limited understanding of the prevalence of concurrent functional vision and hearing impairment (dual sensory impairment) and its contribution to dementia risk. OBJECTIVE To examine the age-specific prevalence of functional dual sensory impairment among older adults, and to investigate the cross-sectional and 7-year longitudinal associations between functional dual sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 41 publications
6
55
0
Order By: Relevance
“…''Dual disorders'' are common in health research and dual trajectory models provide an opportunity to study this phenomenon. Previous studies have found that concurrent sensory impairment such as vision and hearing loss increases the risk of dementia (Kuo et al, 2021b). Gopinath et al (2013) have found dual sensory impairment to be associated with increased mortality with a greater risk of death than that of vision loss or hearing loss alone.…”
Section: Introductionmentioning
confidence: 99%
“…''Dual disorders'' are common in health research and dual trajectory models provide an opportunity to study this phenomenon. Previous studies have found that concurrent sensory impairment such as vision and hearing loss increases the risk of dementia (Kuo et al, 2021b). Gopinath et al (2013) have found dual sensory impairment to be associated with increased mortality with a greater risk of death than that of vision loss or hearing loss alone.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although it is likely that the investigators' overall conclusions remain valid, their approach may have underestimated standard errors and overestimated statistical power for their models. In a study that our group published earlier this year, 3 we reported a significant association between self-reported visual difficulty and dementia in NHATS. Like the study by Pershing et al, our analysis used data from NHATS and included up to 8 years of follow-up from 2011 to 2018.…”
mentioning
confidence: 65%
“…Participants were coded as having a hearing disability if they reported being deaf or if they responded "No" to questions asking if they could hear well enough to use the telephone, carry on a conversation in a room with the TV or radio playing, and carry on a conversation in a quiet room. This method has been used in previous studies with NHATS data (Kuo et al, 2021). Individuals who self-reported vision disability or hearing disability at baseline were followed longitudinally to better understand trajectories of social isolation.…”
Section: Self-reported Hearing Disabilitymentioning
confidence: 99%